Prevalence of hepatitis C serum antibody in autoimmune diseases (2009)
Objective: To evaluate the prevalence of serum antibodies against hepatitis C virus and other infectious agents in a large cohort of well-characterized patients with autoimmune diseases (AID). Methods: We utilized 1322 sera from patients with 18 different AID and 236 sera from healthy controls from the same countries and with similar age and sex distribution. All sera were tested for the presence of serum anti-hepatitis C virus (HCV) antibodies as well as antibodies directed at other infectious agents and autoantibodies. Results: Anti-HCV antibody was detected in 115/1322 (8.7%) of patients with AID and 0.4% of matched healthy controls (P less than 0.0001). The prevalence of anti-HCV antibody was significantly higher in 7/18 different AID (i.e. cryoglobulinemia, mixed cryoglobulinemia pemphigus vulgaris, vasculitis, secondary anti-phospholipid syndrome, Hashimoto's thyroiditis, and inflammatory bowel disease) compared to controls. Patients with AID and serum anti-HCV positivity had an increased prevalence of antibodies against hepatitis B virus, Toxoplasma gondii and Cytomegalovirus as opposed to a lower frequency of serum autoantibodies. Conclusions: The enhanced prevalence of anti-HCV serum antibodies in AID may suggest a role for HCV in tolerance to breakdown, similarly to its established role in mixed cryoglobulinemia. This immune mediated effect does not rule out the role of other infectious agents. © 2009.